2003
DOI: 10.3758/bf03196124
|View full text |Cite
|
Sign up to set email alerts
|

The effects of associations and aging on illusory recollection

Abstract: Younger and older adults (mean years 5 20.5 and 75) studied lists of associated words for a final recognition test. The length (5, 10, or 15 associates) and modality (auditory or visual) of study lists were manipulated within subjects. For both groups, increasing the number of associates increased illusory recollections of a related lure's presentation (measured by source judgments and the Memory Characteristics Questionnaire). This pattern suggests that associative activation of the lure influenced illusory r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
130
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(140 citation statements)
references
References 56 publications
9
130
0
1
Order By: Relevance
“…Such a conceptualization would be most compatible with a lexical-semantic system in which only the singular forms of nouns are stored and pluralization takes place via rule application; there is currently debate about whether this is the case or whether both singular and plural forms are stored in a connectionist network (e.g., Marchman, Plunkett, & Goodman, 1997). From the latter perspective, our findings would suggest that older adults have impaired encoding of the details of experienced episodes, leading to a deficit in item memory that is most easily detected when test lures must be differentiated from highly similar studied items (see also Gallo & Roediger, 2003). 4 It remains for us to explain, from an encoding viewpoint, why older adults do not have a dual benefit of repetition, whereas young adults do.…”
Section: Discussionmentioning
confidence: 81%
“…Such a conceptualization would be most compatible with a lexical-semantic system in which only the singular forms of nouns are stored and pluralization takes place via rule application; there is currently debate about whether this is the case or whether both singular and plural forms are stored in a connectionist network (e.g., Marchman, Plunkett, & Goodman, 1997). From the latter perspective, our findings would suggest that older adults have impaired encoding of the details of experienced episodes, leading to a deficit in item memory that is most easily detected when test lures must be differentiated from highly similar studied items (see also Gallo & Roediger, 2003). 4 It remains for us to explain, from an encoding viewpoint, why older adults do not have a dual benefit of repetition, whereas young adults do.…”
Section: Discussionmentioning
confidence: 81%
“…If this is the case, participants may give believe judgments to inference questions because of a lingering suspicion that the original information was true. However, if the lasting effect of false inferences follows findings in the false memory literature (e.g., Gallo & Roediger, 2003;Geraci & McCabe, 2006), participants may report vividly recollecting the inferences. Each finding would have implications for the approaches one would take to reduce false inferences.…”
Section: Materials and Proceduresmentioning
confidence: 87%
“…We found that people remember facts but believe inferences. On the basis of the false memory literature (e.g., Gallo & Roediger, 2003;Geraci & McCabe, 2006;Roediger & McDermott, 1995), one would have predicted that people would report remembering incorrect inferences. This large literature shows that people often report remembering erroneous information, rather than knowing it or guessing that it occurred.…”
Section: Free Recallmentioning
confidence: 99%
“…In this paradigm participants view a series of words that converge to a common nonpresented theme (e.g., bed, tired, pillow, rest). After studying these items participants tend to falsely remember the non-presented theme sleep (Roediger & McDermott, 1995), a tendency that is magnified in older compared to younger adults Tun, Wingfield, Rosen, & Blanchard, 1998; but see Gallo & Roediger, 2003). This age difference has been attributed to older adults' increased reliance on memory for ''gist'' information (Brainerd & Reyna, 1998) and deficits in source memory (Dodson & Schacter, 2002;Johnson, Hashtroudi, & Lindsay, 1993).…”
mentioning
confidence: 99%